(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
In this article, the author presents the importance of forming econometric skills in students, especially the necessary methods for building trend models and forecasting skills. He also used the case-study method to build trend models and presented cases step by step. He presented the construction of the trend model based on the additive model, analysis and forecasting with the help of cases